Algorithm and framework for tower fault caused by ice overload. (March 2021) - Arias Velásquez, Ricardo Manuel; Mejía Lara, Jennifer Vanessa
Highlights: To establish the root cause analysis method, for towers collapses located in the Andean mountains. Framework and algorithm is proposed for new design associated to ice loads. Ice loads in cables would be dangerous to the towers at the near future. Abstract: In the last years, energy transmission companies has challenges in ice conditions caused by climatic change around the world. Overhead lines could be affected for the ice overload over the cable. Especially in Andean mountains higher than 4500 m above mean sea level (mamsl). The target of this study is to establish the root cause analysis and conditions, for towers collapses located in the Andean mountains and the recommendations at the design stage. It is a contribution to new transmission systems associated to climate change; it has dramatically changed the cold and freezing stages in the Peruvian Andes, if this new considerations has not been implemented, then, the towers could be in a degradation process at the near future.